Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Effects of mycobacterium cell wall fraction on embryo development following in vitro embryo production and pregnancy rates following embryo transfer in virgin dairy heifers - W. Brown; M. Oliveira; R. Reis Silva; K. Woodruff; B. Bisha; D. Demetrio; J. Block (Theriogenology, 2024)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Ancillary data from animal-borne cameras as an ecological survey tool for marine communities - T. K. Chapple; D. Tickler; R. C. Roche; D. T. I. Bayley; A. C. Gleiss; P. E. Kanive; O. J. D. Jewell; S. J. Jorgensen; R. Schallert; A. B. Carlisle; J. Sannassy Pilly; S. Andrzejaczek; et al. (Marine Biology, 2021)
Underwater visual surveys represent an essential component of coastal marine research and play a crucial role in supporting the management of marine systems. However, logistical and financial considerations can limit the availability of survey data in some systems. While biologging camera tag devices are being attached to an increasing diversity of marine animals to collect behavioral information about the focal species, the ancillary imagery collected can also be used in analytical techniques developed for diver-based surveys. We illustrate this approach by extracting ancillary data from shark-borne camera tag deployments focused on the behavior of a White shark ( Carcharodon carcharias) off Gansbaai, South Africa, and a Grey Reef shark ( Carcharhinus amblyrhynchos) within the Chagos Archipelago. Within the giant kelp forest environment of Gansbaai we could determine the spatial density of kelp thali and underlying substrate composition. Within the coral reef environment, the animal-borne video allowed us to determine the approximate percent and type of benthic cover, as well as growth form and genus of corals down to the upper mesophotic zone. We also enumerated fish species-level abundance over reef flat and wall environments. We used established dive-survey methods to analyze video data and found the results to be broadly comparable in the two systems studied. Our work illustrates the broad applicability of ancillary animal-borne video data, which is analogous in type and quality to diver-based video data, for analysis in established marine community survey frameworks. As camera tags and associated biologging technologies continue to develop and are adapted to new environments, utilising these data could have wide-ranging applications and could maximise the overall cost–benefit ratio within biologging deployments.

Behavior and Ecology of Silky Sharks Around the Chagos Archipelago and Evidence of Indian Ocean Wide Movement - David J. Curnick; Samantha Andrzejaczek; David M. P. Jacoby; Daniel M. Coffey; Aaron B. Carlisle; Taylor K. Chapple; Francesco Ferretti; Robert J. Schallert; Timothy White; Barbara A. Block; Heather J. Koldewey; Ben Collen (Frontiers in Marine Science, 2020)
Silky sharks ( Carcharhinus falciformis ) represent a major component of global shark catch, both directly and as bycatch, and populations are declining as a result. An improved understanding of their movement ecology is needed to support conservation efforts. We deployed satellite and acoustic tags (2013–2018) and analyzed historical fisheries records (1997–2009), to investigate the spatial ecology of silky sharks in the central Indian Ocean and a large Marine Protected Area (MPA; 640,000 km 2 ) around the Chagos Archipelago. We observed high fidelity to the MPA, and a sustained diurnal association with a seamount complex, with individuals moving off at night and returning at sunrise. Yet, we also observed large-scale divergent movements in two satellite tagged individuals and documented the furthest recorded displacement distance for a satellite tagged silky shark to date, with one individual moving from the MPA to the Kenyan coast—a displacement distance of 3,549 km (track distance ∼4,782 km). Silky sharks undertook diel vertical migrations and oscillatory diving behavior, spending > 99% of their time in the top 100 m, and diving to depths of greater than 300 m, overlapping directly with typical deployments of purse seine and longline sets in the Indian Ocean. One individual was recorded to a depth of 1,112 m, the deepest recorded silky shark dive to date. Individuals spent 96% of their time at liberty within water temperatures between 24 and 30°C. Historic fisheries data revealed that silky sharks were a major component of the shark community around the archipelago, representing 13.69% of all sharks caught by longlines before the fishery closed in 2010. Over half (55.88%) of all individuals caught by longlines and purse seiners were juveniles. The large proportion of juveniles, coupled with the high site fidelity and residence observed in some individuals, suggests that the MPA could provide considerable conservation benefits for silky sharks, particularly during early life-history stages. However, their high mobility potential necessitates that large MPAs need to be considered in conjunction with fisheries regulations and conservation measures in adjacent EEZs and in areas beyond national jurisdiction.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Biosynthesis and function of terpenoid defense compounds in maize (Zea mays) - Anna K. Block; Martha M. Vaughan; Eric A. Schmelz; Shawn A. Christensen (Planta, 2019)

Ureaplasma parvum causes hyperammonemia in a pharmacologically immunocompromised murine model - X. Wang; K. E. Greenwood-Quaintance; M. J. Karau; D. R. Block; J. N. Mandrekar; S. A. Cunningham; J. M. Mallea; R. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Genetic variants in the folate pathway and risk of childhood acute lymphoblastic leukemia - Catherine Metayer; Ghislaine Scélo; Anand P. Chokkalingam; Lisa F. Barcellos; Melinda C. Aldrich; Jeffrey S. Chang; Neela Guha; Kevin Y. Urayama; Helen M. Hansen; Gladys Block; Vincent Kiley; John K. Wiencke; et al. (Cancer Causes & Control, 2011)

Habitat and behaviour of yellowfin tuna Thunnus albacares in the Gulf of Mexico determined using pop‐up satellite archival tags - K. C. Weng; M. J. W. Stokesbury; A. M. Boustany; A. C. Seitz; S. L. H. Teo; S. K. Miller; B. A. Block (Journal of Fish Biology, 2009)
This study presents the first data on movement, habitat use and behaviour for yellowfin tuna Thunnus albacares in the Atlantic Basin. Six individuals were tracked in the Gulf of Mexico using pop‐up satellite archival tags. Records up to 80 days in length were obtained, providing information on depth and temperature preferences as well as horizontal movements. Thunnus albacares in the Gulf of Mexico showed a strong preference for the mixed layer and thermocline, consistent with findings for this species in other ocean basins. Fish showed a diel pattern in depth distribution, remaining in surface and mixed layer waters at night and diving to deeper waters during the day. The vertical extent of T. albacares habitat appeared to be temperature limited, with fish generally avoiding waters that were >6° C cooler than surface waters. The vertical and thermal habitat usage of T. albacares differs from that of bigeye Thunnus obesus and bluefin Thunnus thynnus , Thunnus orientalis and Thunnus maccoyii tunas. These results are consistent with the results of earlier studies conducted on T. albacares in other oceans.

A Review of Fine Root Dynamics in Populus Plantations - R. M. A. Block; K. C. J. Van Rees; J. D. Knight (Agroforestry Systems, 2006)

Characterization of Aspen ASH, Sand and Log-Yard Waste Mixtures from an Aspen-Based Oriented Strand Board Mill for Use as an Intermediate Landfill Cover - R. M. A. Block; K. C. J. van Rees (Water, Air, & Soil Pollution, 2004)

Mechanized land preparation in forest-based fallow systems: The experience from Eastern Amazonia - M. Denich; K. Vielhauer; M.S. de A. Kato; A. Block; O.R. Kato; T.D. de Abreu Sá; W. Lücke; P.L.G. Vlek (Agroforestry Systems, 2004)

Behaviour of a sharptail mola in the Gulf of Mexico - A. C. Seitz; K. C. Weng; A. M. Boustany; B. A. Block (Journal of Fish Biology, 2002)
A sharptail mola Masturus lanceolatus was tagged and released with a pop‐up satellite archival tag in the Gulf of Mexico and tracked for 61 days. The fish travelled a horizontal distance of 594 km while generally staying in water 20° C. Occasionally the sharptail mola dived to depths >700 m and experienced water colder than 6° C.